Los jueces sin rostro y la aplicación del principio de imparcialidad. - Allauca Vargas, Oscar Ramiro (2023)
The administration of justice is a fundamental pillar for the proper development of a State. Faceless justice emerges as a prevailing need for judges to safeguard their integrity and for society to receive rulings without external influences. The main objective of this research was to describe the characteristics of the system of faceless judges through critical and legal analysis to determine if the principle of impartiality is applied. The unit of analysis is located in the sentences that have been issued by the courts of faceless judges, where the application of the principle of impartiality in the resolutions issued by faceless judges was studied; the researcher assumes a qualitative approach for the study of the legal problem; the inductive, comparative, legal, dogmatic, analytical and descriptive methods have been used. Further, the research is of a basic, comparative analytical, and descriptive type of non-experimental design. The population involved is made up of judges guaranteeing constitutional rights and lawyers in free practice from the city of Riobamba.